Genome-wide characterization of FAD gene family in Xanthoceras sorbifolium Bunge and germplasm assessment - Qinqin Xing; Huijuan He; Zhijun Wang; Yaqiang Li; Xerdiman Didar; Tao Zhou (PLoS ONE, 2025)
Fatty acid desaturases (FADs) play a pivotal role in the accumulation of oils in plant seeds. To elucidate the role of FADs in oil accumulation in the seeds of Xanthoceras sorbifolium, this study employed bioinformatics analysis methods to identify and analyze the FAD gene family. A total of 25 XsFAD genes were unevenly distributed across 11 chromosomes. Systematic phylogenetic analysis revealed that the XsFAD gene family is divided into three branches, with each branch exhibiting similar gene structures. The regulatory elements within the XsFAD gene promoter indicate that XsFAD genes are regulated by multiple factors. Quantitative real-time polymerase chain reaction (qRT-PCR) validation revealed a positive correlation between the expression levels of XsFAD genes and the oil content of X. sorbifolium. By conducting phenotypic measurements of the X. sorbifolium fruit and seeds, as well as quantitative analysis of the XsFAD gene expression, it has been preliminarily identified that the Liudong-5 variety may poseess the potential to be developed into a high-yield oil-producing variety, which may be related to the habitat of the X. sorbifolium germplasm and requires further investagation. In summary, this study provides a foundational understanding of the FAD gene family of X. sorbifolium, and the research outcomes will contribute to the theoretical basis for the selection of high-yielding oil varieties of X. sorbifolium in the Xinjiang region, as well as further genetic breeding and cultivation system studies.